Prayer as a Medical Media for Pellet Victim in the Naqsabandiyah Thoriqah - Husnul Qodim (Khazanah Sosial, 2022)
This paper examines the concept of prayer applied by Naqsabandiyah Thoriqah activists at the Suluk Babul Khairat House in preventing and treating pellet victimThis research is field research using qualitative methods. Data collection techniques were carried out by open observation, in-depth interviews, and personal documentation, while the data processing techniques were carried out using descriptive-analytical techniques. In this study the authors found that the medical practice carried out by Caliph Misno at the Suluk Babul Khairat House did not serve medical treatment, but psychological diseases caused by pellet or witchcraft, witchcraft, and various other non-medical diseases. Besides that, The author also found that the prevention technique practiced by Caliph Misno in treating these non-medical diseases was carried out by giving Naqsabandiyah tariqah practices, such as: dhikr ismu dzat, (mentioning Allah in the heart), dhikr Nafi isbat (saying Laa Ilaha Illallah). , it is better to participate in carrying out khataman tawajuh. While the treatment technique is carried out using six stages, namely; intention, reading istighfar three times, reading dhikr ismu dzat, reading surah Al-Fatihah, Al-Ikhals, Al-Falaq, An-Nass, and Ayat Kursi, channeling the energy of the prayer into the water, and the last one is closed by reading a prayer for client recovery. dhikr Nafi isbat (calling Laa Ilaha Illallah), it is even better to participate in carrying out khataman tawajuh. While the treatment technique is carried out using six stages, namely; intention, reading istighfar three times, reading dhikr ismu dzat, reading surah Al-Fatihah, Al-Ikhals, Al-Falaq, An-Nass, and Ayat Kursi, channeling the energy of the prayer into the water, and the last one is closed by reading a prayer for client recovery. dhikr Nafi isbat (calling Laa Ilaha Illallah), it is even better to participate in carrying out khataman tawajuh. While the treatment technique is carried out using six stages, namely; intention, reading istighfar three times, reading dhikr ismu dzat, reading surah Al-Fatihah, Al-Ikhals, Al-Falaq, An-Nass, and Ayat Kursi, channeling the energy of the prayer into the water, and the last one is closed by reading a prayer for client recovery. This research is expected to contribute to the development of the study of thoriqah in Indonesia, especially the Naqsabandiyah congregation in Deli Serdang district.